Survival of the Immature Stages of the Malaria Vectors Anopheles pseudopunctipennis and Anopheles argyritarsis (Diptera: Culicidae) in Northwestern Argentina - Galante, Guillermina B. (2014)
In order to optimally time the application of control measures to reduce populations of malaria vectors, program managers need to know precisely when the vulnerable larval stage will be most abundant at each specific breeding site. Therefore at 4 different breeding sites of the malaria vectors, Anopheles pseudopunctipennis Theobald and Anopheles argyritarsis Robineau-Desvoidy in northwestern Argentina, we recorded the calendar dates during spring and summer when different life stages appeared, and in each of these 2 seasons, we measured the duration of each life stage and the probability that it would transition to the subsequent stage or die. Larval samples were collected during the spring and summer of 2008-2009 at 4 localities in northwestern Argentina. These larvae were reared individually in plastic containers in which the volume of water was kept constant, temperature and photoperiod were controlled, and a standard amount of food was provided each day. The data were analyzed by multistate models, a nonparametric model of survival without covariates, a survival model with covariates, a Cox-type survival model with specific co-variates, and models of reduced rank. We collected 1,643 larvae of which 1,404 reached adulthood. Of these 1,119 were An. pseudopunctipennis, and 285 were An. argyritarsis. Both An. pseudopunctipennis and An. argyritarsis were abundant in autumn (55.3% and 66.7%, respectively). Considerably more individuals transitioned from larvae to pupae than from pupae to adults. The probability of an individual remaining in the larval stage for the first 2 days was close to 100% and then decreased. The transition from the larval stage to death was significant in the summer. The breeding site at Rosario de la Frontera exhibited a particularly significant effect on the transition from the larval stage to death, i.e., greatly increased larval mortality. The results obtained in the present study are substantial contributions to the bionomics of An. pseudopunctipennis and An. argyritarsis. According to our results, mosquito source management programs should be focused on the larval stage during the summer season and principally at Rosario de la Frontera River. These actions could substantially reduce the production of the adult vectors and potentially reduce transmission of malaria in northwestern Argentina.